Higher-order Displacement Model for Cylindrical Bending of Laminated and Sandwich Plates Subjected to Environmental Loads - Nitin S. Naik; Atteshamuddin Sayyad (Mechanics of Advanced Composite Structures, 2021)
In this research article, thermal and hygrothermal stress analysis of composite layered and sandwich plate having one dimension infinitely long and simply supported on the edges is presented using a new fifth-order theory.  The proposed theory considers, the effect of thickness stretching. The present theory uses a polynomial shape function to account for transverse shear deformation using the expansion of thickness up to the fifth-order while to consider the effect of thickness stretching the derivative of shape function is used in the transverse displacement. In this theory, the shear strain variation is assumed to be parabolic across the thickness.  The present displacement field satisfies zero shear stress condition both at the top and bottom surfaces and avoids the use of a shear correction factor.  The governing equations are derived using the virtual work principle.  For solution of problem, Navier’s solution technique is used.  The results generated using the present theory are compared with the existing elasticity solution wherever it is available.  However, many results for the cylindrical flexural analysis of laminated and sandwich plates subjected to environmental loading are presented for the first time in this paper.